Development Of Google Site As An Interactive Learning Media Integrated With Islamic Values - Wulandari, Dyah Retno; Sholihat, Neng; Purwanto, Hadi; Jehloh, Nurulhuda (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
The research of the study was to determine the feasibility of Google Site learning media integrated Islamic values by utilizing advances in technology and student perceptions. The type of research is R&D using the ADDIE model design. The subjects of this study were researchers, material, religious, and media experts, as well as 61 seventh-grade students of junior high school. The data collection technique is to use the interview method, observation and validation sheet, and response questionnaire. Data analysis is quantitative according to the ADDIE model development procedure. The results showed that the feasibility of the product from material expert validation obtained a score of 97%, religious expert validation 100%, media expert validation with a score of 96%, and educator practicality obtained 91% and 95% learner response. Based on the results obtained, the interactive learning media of the integrated solar system of Islamic values is feasible and practical to be used to help learn and add insight into the relationship of material with Islamic values at junior high school.ABSTRAK: Tujuan penelitian adalah untuk mengetahui kelayakan media pembelajaran google site diintegrasikan nilai-nilai islam dengan memanfaatkan kemajuan teknolog dan persepsi peserta didik. Jenis penelitian adalah R&D dengan menggunakan desain model ADDIE. Subjek penelitian ini yaitu peneliti, ahli materi, agama dan media, serta 61 peserta didik kelas VII sekolah menengah pertama. Teknik pengumpulan data adalah dengan menggunakan metode wawancara, observasi dan lembar validasi serta angket persepsi. Analisis data yaitu menggunakan deskriptif kuantitatif sesuai prosedur pengembangan model ADDIE. Hasil penelitian menunjukkan bahwa kelayakan produk dari validasi ahli materi memperoleh skor 97%, validasi ahli agama 100%, validasi ahli media dengan skor 96%, prktikalitas pendidik memperoleh 91% dan respon perserta didik 95%. Berdasarkan hasil yang diperoleh maka media pembelajaran interaktif sistem tata surya terintegrasi nilai-nilai islam layak dan praktis digunakan untuk membantu belajar dan menambah wawasan keterkaitan materi dengan nilai-nilai islam di sekolah menengah pertama.